Antenatal Care Service Utilization of Pregnant Women Attending Antenatal Care in Public Hospital During the COVID-19 Pandemic PeriodAntenatal Care Service Utilization of Pregnant Women Attending Antenatal Care in Public Hospital During the COVID-19 Pand (Medical Forum Monthly, 2021)
Objective: To evaluate antenatal care utilization of pregnant women attending care during COVID-19 pandemic.Study Design: Cross sectional studyPlace and Duration of Study: This study was conducted at the Study was conducted at outpatient department of Gynecology and Obstetrics Sindh Government Hospital, Qasimabad, Hyderabad, from February 2021 to July 2021.Materials and Methods: Three hundred and twenty patients were enrolled in the study. Main variables of study were antenatal visits, education of mother, residential area (rural and urban), and depression during COVID-19 and number of visits. Data analysis was done by using SPSS version 23. Mean and frequency were calculated, test of significance t-test and chi square test were applied. P value ≤0.05 was taken as significance.Results: The mean height of fundus of the patients was 29.21±4.29cm. Majority of the patients 92.2% was longitude lie. Cephalic was the most common presenting part i.e. 82.8%. Fetal movement and fetal heart sound were positive in 87.2% and 89.7%, respectively. The mean antenatal care visits of the patients were 2.63±1.77 times. Most of the patients 74.7% had ≤3 antenatal care visits. 6.9% patients had positive covid-19 while 5.3% went to isolation.Conclusion: Findings of this reveal that COVID-19 pandemic reduced the utilization of antenatal health care facilities among pregnant women. Thus, the residency, age of mother and educational status are main contributing factors involved in use ANC facilities.